Navigating Technological Obsolescence: Analysis and Reconstruction of Stockhausen's Mikrophonie I. - Roth, Timothy (Contemporary Music Review, 2023)
This article outlines analytical methods for preparing and interpreting Karlheinz Stockhausen's sextet Mikrophonie I (1964) for tam-tam and electronics. Would-be performers of this work face significant accessibility issues: Stockhausen's recommended equipment—especially the electronic filter used to process the tam-tam's sound—is extremely rare. These issues often necessitate performers finding alternative solutions for equipment. Mikrophonie I is one of several works for live electronics that have become increasingly difficult to program, due to the obsolescence of the technology required to perform them. Performers often reconstruct the necessary electronics digitally, using software such as Max/MSP. Wetzel [(2006). "A Model for the Conservation of Interactive Electroacoustic Repertoire: Analysis, Reconstruction, and Performance in the Face of Technological Obsolescence." Organised Sound 11 (3): 273–284. https://doi.org/10.1017/S1355771806001555] describes a three-stage model for this reconstructive process that foregrounds the need for performer-led analysis. Using Mikrophonie I as a case study, I expand on Wetzel's model to navigate the reconstruction through two main analytical perspectives: the prioritisation of sound or process. These methods are then applied to my realisation process of Mikrophonie I. I describe the process of constructing a digital filter in Max/MSP based on a patch created by Christopher Burns [(2002). "Realizing Lucier and Stockhausen: Case Studies in the Performance Practice of Electroacoustic Music." Journal of New Music Research 31 (1): 59–68. https://doi.org/10.1076/jnmr.31.1.59.8104] and compare different interface options for using the filter in performance. Referring to previous recordings by the Stockhausen Ensemble (1965) and the percussion ensemble red fish blue fish (2014), I show how creative interpretations can help ensembles overcome the perceived shortcomings of their available tam-tam. Beyond the specifics of reconstructing the technology required for performing Mikrophonie I, this article underlines the indispensability of analysis for performers who specialise in works with obsolescent technology.